The Improvement of the Grant and Social Assistance Innovation Model in the Realization Report of the Bandung City Budget: Peningkatan Model Inovasi Hibah dan Bansos dalam Laporan Realisasi APBD Kota Bandung - Novia Mega Pratiwi, Novia Mega Pratiwi (Pusat Riset dan Inovasi Nasional, 2022)
The management of grants and social assistance funds is a problem in several local governments. The problem of managing grants and social assistance is transparency and accountability. Bandung City Government. The focus of the research is analyzing the innovation model of aid policies based on improving public services by innovating through grants and social assistance funds, as well as examining the inhibiting and supporting factors and designing an effective innovation model. social assistance. This study uses descriptive qualitative research methods (more specifically the “action research” method) to clearly see the management of grants and social assistance through grant and social assistance innovations. The results of this study found that this innovation was very beneficial in the management of grants and social assistance funds, especially increasing transparency and accountability. This innovation has a positive impact on the management of grants and social assistance funds that can be replicated by other regions.